Utilization of Information Technology-Based Learning Media for Supporting Active Learning Activities at Middle School (SMP) Negeri 2 Pantai Labu - Syahputra, MR; Mardiningsih; Rambe, Isnaini Halimah (Talenta Publisher, 2020)
The community service that will be carried out in this research is entitled